EDUKASI STIMULASI TUMBUH KEMBANG MELALUI PIJAT BAYI DI POSYANDU SERUNAI KELURAHAN PIAI TANGAH KECAMATAN PAUH KOTA PADANG - Hamidatul Yuni; Melisa Yenti; Novrida Yanti; Nadia Putri Amara (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2021)
In some areas in Padang City, we still often hear parents who have toddlers taking their children to a traditional birth attendant for a massage for various reasons. In addition, the baby's mother does not yet have independent skills in doing massage to babies. Baby massage is a tactile stimulation that has physiological effects in the body. Baby massage can also cause the baby's interaction with the mother to be more positive, the baby to be calmer and his sleep patterns to be more regular. Serunai Posyandu is one of the posyandu that has never received education about baby massage. The purpose of this service is to introduce proper baby massage to mothers who have babies at the Posyandu Serunai, so it is hoped that mothers can apply good and correct baby massage at home to stimulate baby growth and development. The method used in this activity is counseling and demonstration of baby massage. Before the activity begins, an initial survey is carried out, then the implementation of the activity is carried out with counseling, and demonstration of the correct way of baby massage. Finally, monitoring evaluation is carried out, seen from the frequency of implementation of independent baby massage by mothers at their respective homes for one month after the demonstration using a checklist sheet. The results of this activity were from 11 mothers of babies, 100% of mothers did independent baby massage at home, and 36.4% of mothers routinely did independent baby massage for one month, 28.5% of infants experienced weight gain of 0.3-0.5 kg . It is hoped that in the future the Puskesmas will schedule baby massage counseling at all posyandu for infants and toddlers.